Somatostatin analogues in the control of neuroendocrine tumours: efficacy and mechanisms. - Grozinsky-Glasberg, S; Shimon, I; Korbonits, M; Grossman, AB (2008)
Neuroendocrine tumours (NETs) represent a heterogeneous family of neoplasms, which may develop from different endocrine glands (such as the pituitary, the parathyroid or the neuroendocrine adrenal glands), endocrine islets (within the thyroid or pancreas) as well as from endocrine cells dispersed between exocrine cells throughout the digestive and respiratory tracts. The development of somatostatin analogues (SSA) as important diagnostic and treatment tools has revolutionised the clinical management of patients with NETs. However, although symptomatic relief and stabilisation of tumour growth for various periods of time are observed in many patients treated with SSA, tumour regression is rare. Possible mechanisms when this does occur include antagonism of local growth factor release and effects, probably including activation of tyrosine and serine-threonine phosphatases, and indirect effects via anti-angiogenesis. The development of new SSA, new drug combination therapies and chimaeric molecules should further improve the clinical management of these patients, as should a more complete understanding of their mode of action.